Dust and Cold Gas Properties of Starburst HyLIRG Quasars at z ∼ 2.5 - Liu, Feng-Yuan; Dai, Y. Sophia; Omont, Alain; Liu, Daizhong; Cox, Pierre; Neri, Roberto; Krips, Melanie; Yang, Chentao; Wu, Xue-Bing; Huang, Jia-Sheng (The Astrophysical journal, 2024)
Some high- z active galactic nuclei (AGNs) are found to reside in extreme star-forming galaxies, such as hyperluminous infrared galaxies (HyLIRGs), with AGN-removed L IR of >10 13 L ⊙ . In this paper, we report NOEMA observations of six apparent starburst HyLIRGs associated with optical quasars at z ∼ 2–3 in the Stripe 82 field, to study their dust and molecular CO properties. Five out of the six candidates are detected with CO(4–3) or CO(5–4) emission, and four in the 2 mm dust continuum. Based on the linewidth– L CO ( 1 − 0 ) ′ diagnostics, we find that four galaxies are likely unlensed or weakly lensed sources. The molecular gas mass is in the range of μ M H 2 ∼ 0.8 – 9.7 × 10 10 M ⊙ (with α = 0.8 M ⊙ K km s − 1 pc 2 − 1 , where μ is the unknown possible gravitational magnification factor). We fit their spectral energy distributions, after including the observed 2 mm fluxes and upper limits, and estimate their apparent (uncorrected for possible lensing effects) star formation rates ( μ SFRs) to be ∼400–2500 M ⊙ yr −1 , with a depletion time of ∼20–110 Myr. We notice interesting offsets, of ∼10–40 kpc spatially or ∼1000–2000 km s −1 spectroscopically, between the optical quasar and the millimeter continuum or CO emissions. The observed velocity shift is likely related to the blueshifted broad-emission-line region of quasars, though mergers or recoiling black holes are also possible causes, which can explain the spatial offsets and the high intrinsic star formation rates in the HyLIRG quasar systems.